Friction-induced artifact in atomic force microscopy topographic images - Thales Fernando Damasceno Fernandes (2014)
In Contact Mode Atomic Force Microscopy (CM-AFM), a cantilever with a sharp tip on its end is employed to acquire topographic information. Such acquisition is normally made by monitoring the deflection of the cantilever when it is in contact with the surface being scanned and using deflection variations as a feedback signal to the control electronics in order to keep the deflection constant (also known as constant force imaging mode in the literature). However, there is a major problem with this approach since, in most cases, a constant force scanning is not possible: frictional forces, besides normal forces, may bend the cantilever. Such additional bending (deflection) needs to be considered in the formulation of the problem. The present dissertation investigates how these forces (frictional and normal) can give rise to a topographic artifact when scanning along the cantilever axis direction. Such artifact is even more dramatic when the friction coefficient of the sample changes from region to region. This effect is studied experimentally, with a sample composed of graphene monolayer atop silicon oxide. The observed artifact, caused by frictional forces, causes the graphene to appear either thicker or thinner than it really is depending on scan direction. A theoretical examination is also made both with analytical methods (Euler-Bernoulli beam theory) and a simulation on COMSOL Multiphysics package. The theory not only predicts the artifact, but also indicates how it can be completely avoided by changing the scanning angle to the perpendicular direction of the cantilever axis.